2020
DOI: 10.1002/jcb.29613
|View full text |Cite
|
Sign up to set email alerts
|

miR‐133a‐3p/FOXP3 axis regulates cell proliferation and autophagy in gastric cancer

Abstract: Although many methods and new therapeutic drugs have been developed, the overall survival rate and long-term survival rate of patients with gastric cancer (GC) are still not satisfactory. In this study, we investigated the effects of microRNA miR-133a-3p and transcription factor FOXP3 on proliferation and autophagy of GC cells and their interactions. Our results showed that knockdown of FOXP3 increased the proliferation and autophagy of GC cells.The relationship between FOXP3 and autophagy has not been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 54 publications
1
20
1
Order By: Relevance
“…Forkhead protein 3 (FOXP3), a forkhead transcription factor and specific marker for T regulatory (Treg) cells, can downregulate TP53 by directly targeting its promoter and inhibiting its transcription. In contrast to previous studies, miR-133a-3p could promote the proliferation and autophagy in different gastric cancer cell lines by binding to the 3′-UTR of FOXP3 [26]. In dedifferentiated liposarcoma (DDLPS), loss of miR-133a could reduce oxidative metabolism, supporting the tumor Warburg effect.…”
Section: Mir-133a In Autophagy and Metabolismcontrasting
confidence: 72%
“…Forkhead protein 3 (FOXP3), a forkhead transcription factor and specific marker for T regulatory (Treg) cells, can downregulate TP53 by directly targeting its promoter and inhibiting its transcription. In contrast to previous studies, miR-133a-3p could promote the proliferation and autophagy in different gastric cancer cell lines by binding to the 3′-UTR of FOXP3 [26]. In dedifferentiated liposarcoma (DDLPS), loss of miR-133a could reduce oxidative metabolism, supporting the tumor Warburg effect.…”
Section: Mir-133a In Autophagy and Metabolismcontrasting
confidence: 72%
“…Shi et al (33) reported that downregulation of miR-133a-3p promotes the proliferation and invasion of breast cancer cells. Li et al (34) suggested that miR-133a-3p promotes autophagy in gastric cancer cells by negatively regulating forehead box P3. The present study identified decreased miR-133a-3p expression in NSCLC cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…11,14,16 It was recently found that the functions of FOXP3 are also controversial in the progression of gastric cancer (GC). [18][19][20] For instance, overexpression of FOXP3 suppresses GC cell growth in vivo, 18 and silencing FOXP3 expedites the proliferation of GC cells in vitro. 19 By contrast, FOXP3 is upregulated in GC tissues, and overexpression of FOXP3 facilitates cell proliferation, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] For instance, overexpression of FOXP3 suppresses GC cell growth in vivo, 18 and silencing FOXP3 expedites the proliferation of GC cells in vitro. 19 By contrast, FOXP3 is upregulated in GC tissues, and overexpression of FOXP3 facilitates cell proliferation, migration, and invasion. These effects are reversed by FOXP3 loss-offunction mutations in GC cells.…”
Section: Introductionmentioning
confidence: 99%